2022
DOI: 10.21847/1728-9343.2022.3(2).263601
|View full text |Cite
|
Sign up to set email alerts
|

Social cohesion and intercultural studies in the educational community

Abstract: The article shows the important role of social cohesion as a social phenomenon, its impact on the development of society and intercultural communication. The social role of trust, in particular, in the development of social cohesion, is also shown. Social cohesion acquires acute relevance and importance in the current time of social transformations, as cohesion allows communities overcome various fluctuations and changes. The social cohesion as complex social phenomenon has been analyzed in the focus of interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 8 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…The authors obtained the results by comparing the level of social cohesion of the university community in 2020, which takes place in the context of the COVID-19 pandemic, with the indicators of 2019 and 2022, before and after the Russian invasion. The data obtained and analyzed in the study showed that the level of cohesion varies moderately Source: (Dielini M. et al, 2022) Vol. 8 No.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The authors obtained the results by comparing the level of social cohesion of the university community in 2020, which takes place in the context of the COVID-19 pandemic, with the indicators of 2019 and 2022, before and after the Russian invasion. The data obtained and analyzed in the study showed that the level of cohesion varies moderately Source: (Dielini M. et al, 2022) Vol. 8 No.…”
Section: Discussionmentioning
confidence: 97%
“…The area "Orientation towards the common good" reflects how people are oriented towards the community as a whole, how they understand dependence on each other and responsibility. In general, the indicator of this area has a slight increase from 3.24 (2019) to 3.29 (2020) and a significant increase in January 2022 to 3.47 with a slight decrease during the war by 0.01 points, but there are some differences between groups Source: (Dielini M. et al, 2022) Vol . 8 No.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations